2007
DOI: 10.2341/06-54
|View full text |Cite
|
Sign up to set email alerts
|

Restoration Interface Microleakage Using One Total-etch and Three Self-etch Adhesives

Abstract: The common belief that simpler, speedier, more user-friendly adhesives always reduce technique sensitivity should be revaluated. Clinicians should resist the attraction of new, faster, easier-use materials and ask for laboratory and clinical studies before switching to a new material. SUMMARYThis study evaluated the efficacy of a total-etch and three self-etch adhesives in reducing microleakage after three months water storage and thermocycling.Thirty freshly extracted caries-free human premolars and molars we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 24 publications
1
47
1
5
Order By: Relevance
“…5). These findings were consistent with those of previous studies, which reported that resin tags made only a minor contribution to bond strength 7,31,32) . As a result, the shear bond strengths obtained with Clearfil SE Bond were statistically similar (p=0.076) to those obtained with Solobond Plus in this study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…5). These findings were consistent with those of previous studies, which reported that resin tags made only a minor contribution to bond strength 7,31,32) . As a result, the shear bond strengths obtained with Clearfil SE Bond were statistically similar (p=0.076) to those obtained with Solobond Plus in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Mild self-etch adhesives produce hybrid layers thinner than totaletch systems 7) . In this study, the SEM images of specimens prepared from the adhesive systems showed difference in surface texture between the two systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Changing the gap dimensions between bonded interface also allows microleakage. 14,15 The self-etch systems do not require separate etching and priming steps unlike total etch systems 16 ; another concern with the self-etch systems is the presence of water or solvent and it also allows water diffusion, which affects the integrity of restorative interface. 17 Some self-etch adhesives have limited diffusion through smear layer due to their weak acidity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there have been some arguments on the efficacy of the all-in-one adhesive systems on sealing capability of the restorations 18,19) . However, little information is available on internal adaptation of a composite restoration using all-in-one adhesive systems with a flowable composite lining.…”
Section: Introductionmentioning
confidence: 99%